Penggunaan Material Pasir Tayan Pada Campuran Beton - Arditianto, Yanuar; Prabowo, Agung; Pramesty, Elya Arum; Ramadhan, Abil; Hamka, Achmad Chaerul; Herol, Herol (Universitas Pelita Bangsa, 2024)
Concrete is a building material produced by mixing fine aggregate, coarse aggregate, Portland cement, and water. The design of concrete must be in accordance with applicable standards, the process and materials used must meet the main criteria, namely strength, high compressive strength, and easy workmanship. In addition, it must also meet the criteria of being durable, inexpensive, and wear-resistant, among others. In concrete there are two categories of aggregates required, namely fine aggregate and coarse aggregate, the function of the aggregate in the concrete mixture is as a filler, hence the need for good binding and filling properties. The percentage of aggregate used in concrete is very large, so aggregate contributes to the strength of concrete. The research method used materials in accordance with the reference SNI 03-2834-2000. The fine aggregate used is Tayan Sand material from a river in the West Kalimantan area, and the coarse aggregate comes from Rumpin, Bogor. Mix Design is a mixture proportion of the constituent materials that have been tested, it is intended that the proportion of the mixture can meet the strength requirements. The fine and coarse aggregates used qualitatively meet the requirements as concrete constituent materials. From the parameters of cleanliness, gradation, specific gravity, absorption, and organic content are still within the tolerance range of material acceptance specifications.